2019
DOI: 10.1177/2474126419861850
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopy-Assisted Vitrectomy Outcomes During Silicone Oil Removal After Complex Retinal Detachment Repair

Abstract: Purpose: This retrospective study recorded intraoperative findings during silicone oil removal and postoperative anatomical outcomes comparing endoscopy-assisted pars plana vitrectomy (E-PPV) vs pars plana vitrectomy (PPV) alone after proliferative vitreoretinopathy (PVR)-related retinal detachment (RD) repair. Methods: This single-center retrospective study included patients who underwent PPV for silicone oil removal after RD with PVR from July 2009 to January 2017. Patients with diabetic tractional RD, histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
(47 reference statements)
0
4
0
Order By: Relevance
“…These findings could explain why in cases of posterior PVR the reattachment rate was higher in the E-PPV group. In addition, as seen in one of our previous studies [ 15 ], during silicone oil removal the most common intraoperative endoscopy finding was contraction of previous retinectomy in patients with anterior and/or posterior PVR.…”
Section: Discussionmentioning
confidence: 53%
“…These findings could explain why in cases of posterior PVR the reattachment rate was higher in the E-PPV group. In addition, as seen in one of our previous studies [ 15 ], during silicone oil removal the most common intraoperative endoscopy finding was contraction of previous retinectomy in patients with anterior and/or posterior PVR.…”
Section: Discussionmentioning
confidence: 53%
“…17,[20][21][22][23] A recent retro spective study of 33 eyes with endophthalmitis managed with endoscopicassisted vitrectomy suggested that the use of the modality allowed for earlier intervention in cases with poor visualization, which likely reduces the organism load and helps contain the infection. 24 In RD repair, endoscopy is useful, 25 with some studies suggesting improvement in outcomes 26,27 and visualization of retinal breaks. 28 A retrospective study of 101 eyes found that endoscopyassisted vitrectomy achieved better reattachment rates in complex RD and advanced proliferative vitreoretinopa thy (PVR), 26 likely as a result of improved visualization of pathologic structures.…”
Section: Discussionmentioning
confidence: 99%
“…Another retrospective study of 54 eyes found that during silicone oil removal, a change from surgical to endoscopic management in 65.4% of cases was associated with a higher reattachment rate. 27 Endoscopy has been used to guide epiretinal membrane peeling 29 in cases of retained lens fragments, a dislocated lens, or retained silicone oil 30 and is useful during PVR removal. [31][32][33][34] In cases of a large subretinal hemorrhage and fibrovascular pigment epithelial detachment, including choroidal neovascu larization, endoscopy can be used for hemorrhage removal without the need for a large retinotomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation